Understanding the Age Differences in Adopting WFTs: An Extension of the UTAUT2 Model (Global Journal of Management and Business Research, 2023)
Though the use of Wearable Fitness Trackers (WFT) is advancing at an unprecedented pace in developed countries, Bangladesh is still fall behind far away to cope with the proliferate features of advanced technologies, whereas age differences play a vital role for technology adoption especially WFT devices in the context of developing countries. Thus, this study, based on the factors used in Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) along with an additional construct 'Health consciousness', explore the relationship among the endogenous and exogenous variables to develop a clear-foresightedness regarding the WFT adoption in Bangladesh. To achieve this, a survey was employed to collect primary data from 288 WFT users. The data were analyzed using the Partial Least Squares (PLS) method, a statistical analysis technique based upon Structural Equation Modeling (SEM). However, this study explored that hedonic motivation, health consciousness, effort expectancy, facilitating conditions, habit as well as performance expectancy (p< 0.05) are the most cardinal factors that have a strong influence on behavioral intention of the users to adopt WFT devices. Moreover, the impact of effort expectancy, habit, health consciousness on intention-to-use of WFT is further multiplied the usage behavior by the virtue of the moderating effect of the age differences.
Keywords: WFT; adoption; UTAUT2 model; age; developing countries